Genetic diversity of native chicken based on analysis of D-Loop mtDNA marker - Sartika, Tike; Duryadi, D; Mansjoer, S.S; Gunawan, B (Indonesian Journal of Animal and Veterinary Sciences, 2000)
Production was carried out using control region/D-loop mtDNA marker. The base population of native chicken was selected from subpopulation at Cianjur, Jatiwangi, Depok, Bogor I, and Bogor 2. Samples from each population was 10 heads and 2 samples Green Jungle Fowl (Gallus various) from East Java as out Group samples. Two primers binding conserved tRNA Phenylalanine gene and tRNA Glutamine gene were DNA Heavy stranded HI255 (5-CATCTTGGCATCTTCAGTGCC-3) and DNA Light stranded Ll6750 (5-AGGACTACGGCTTGAAAAGC-3) was used to amplify D-Ioop mtDNA chicken. PCR-RFLP methods with 6 restriction enzymes 4 cutter such as, Alul (AGâCT), Hpall (CâCGG), Mbol (âGATC), Rsal (GTâAC), NlaIII (CATGâ) and HaeIII (GGâCC) were used to detect polymorphism within and between subpopulation. Result of experiment show that mtDNA which was amplified by PCR was 1320 bp, consist of 1227 bp control region/D-loop, 45 bp tRNA Glutamine gene and 48 bp tRNA Phenylalananine gene. PCR product which were digested from 6 endonucleases enzyme show that native chicken within and between population was monomorphic and if its compare with Green Jungle Fowl was polymorphic. Â  Key words: Native chicken, genetic diversity, mtDNA